Athlete's perceptions of a "quarantine" training camp during the COVID-19 lockdown - Washif, J.-A.; Fuzyma Ayu Mohd Kassim, S.; Lew, P.; Sheau Miin Chong, C.; James, C. (Frontiers in Sports and Active Living, 2021)
Globally, COVID-19-related movement restrictions have caused significant disruption to athlete`s training and sporting competitions. `Quarantine` camps are one approach to maintain sport-specific training, whilst minimising the risk of COVID-19 transmission between athletes and society. This cross-sectional study investigated the effects of a `quarantine` training camp on athlete`s routines and wellbeing, performance support, perceived stress and sleep behaviours. A survey was completed at the end of a 30-day `quarantine` camp, by 76 elite athletes (17-46 years), predominantly (~80%) Olympic/Paralympic and/or world championship representatives. Athletes described their experiences in comparison to; pre-lockdown training and/or training during `lockdown` (immediately prior to the `quarantine` camp). Compared to `lockdown`, the `quarantine` camp revealed improvements (p<0.05; 0.33 = d = 0.90) in access to sport-specific training (28.6%), recovery facilities (22.2%), nutritional choices (17.5%), mental (12.4%) and emotional (11.4%) health, training motivation (20.0%); and perceived stress (7.4%, d= -0.27, p= 0.026). The camp resulted in a lower sleep duration (-8.5%, d= -0.73, p= 0.014), but an improved global sleep behaviour score (-5.6%, d= -0.22, p= 0.001). During the camp, the performance support athletes received was not different to pre-lockdown (p>0.05), but there was greater sports massage (20.4%, d= 0.39) and physiotherapy usage (18.1%, d= 0.36) (both p<0.05). The adverse effects of lockdown were restored during the camp. A `quarantine` camp may offer comparable training experiences to pre-lockdown training, without inducing additional perceived stress. Coaches and sporting organisations may consider this approach as part of a virus mitigation strategy, whilst maintaining sport-specific training.